Identifying the structure of students’ argumentation in covariational reasoning of constructing graphs - Sutini Sutini; Iffana Fitrotul Aaidati; Kusaeri Kusaeri (Beta: Jurnal Tadris Matematika, 2020)
[English]: This study aimed to identify students’ claim, evidence, and reasoning in covariational reasoning of constructing the graphs of a function. Covariational reasoning is one of the approaches to solve the problems of function. The study involved thirty grade 11 students. Data was collected through a covariation test and interview. The results of the test were grouped based on the criteria of mental action of covariational reasoning (Carlson et al., 2002), then the students who solve correctly two or three problems in the test were selected as the subjects. The interview data were analyzed to confirm and further dig students' structure of argumentation. The findings of this study indicate that only one student fulfils five mental actions of covariational reasoning; meanwhile, the other three students have similar components of argumentation which do not meet the mental actions. The claim and reasoning used by the latter students in covariational reasoning to construct graph are not identified in mental action 5 and the evidence is not found in mental action 3 (major coordination of change), mental action 4 (coordination the average rate of change), and mental action 5 (coordination of the instantaneous rate of change). Keywords: Argumentation, Claim, Evidence, Reasoning, Covariational reasoning [Bahasa]: Penelitian ini bertujuan untuk mengidentifikasi klaim, bukti, dan alasan siswa pada penalaran kovariasional dalam mengonstruk grafik fungsi. Penalaran kovariasional merupakan salah satu pendekatan dalam menyelesaikan permasalahan fungsi. Penelitian ini melibatkan 30 siswa kelas 11. Pengumpulan data dilakukan menggunakan tes kovariasi dan wawancara. Data hasil hasil tes kovariasi siswa dikelompokkan berdasarkan kriteria aksi mental penalaran kovariasional (Carlson et al., 2002), kemudian dipilih siswa yang mampu menyelesaikan minimal dua soal kovariasi. Data hasil wawancara dianalisis untuk mengonfirmasi dan menggali lebih dalam argumentasi siswa. Hasil penelitian menunjukkan hanya satu siswa yang memenuhi lima aksi mental penalaran kovariasional sedangkan ketiga siswa lain memiliki persamaan komponen argumentasi yang tidak memenuhi aksi mental. Untuk ketiga siswa tersebut, klaim dan alasan yang digunakan dalam membangun grafik fungsi tidak berada pada aksi mental 5 sedangkan bukti tidak berada pada aksi mental 3 (koordinasi besar perubahan), aksi mental 4 (koordinasi laju perubahan rata-rata), dan aksi mental 5 (koordinasi laju perubahan sesaat). Kata kunci: Argumentasi, Klaim, Bukti, Alasan, Penalaran kovariasional